The Development of Tuition Centre Management System Using Laravel Framework and Ethereum Blockchain - ZAINUDIN, FATIN NADIA; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2025)
Technology integration in academic management helps solve problems like manual work, poor communication, and unclear tutor qualifications. Aimi An Najjah tuition centre faces these issues. This study introduces a Tuition Centre Management System with blockchain to improve operations, automate tasks, and build trust. The objectives are to design, develop using web-based technology, and test the system through alpha and beta testing. The system includes student information management, attendance tracking, fee payment handling, timetable generation, and tutor certificate verification using blockchain. It was built using Laravel for the backend, HTML, CSS, and JavaScript for the frontend, and MySQL for data management. A prototyping model was used to match user needs. User Acceptance Testing results show that 77.4% of users are very satisfied, and the rest are satisfied. The system reduces errors, improves efficiency, and strengthens communication. Blockchain ensures tutor credentials are clear and secure. It sets a new standard for digital use in education with future mobile and scalability upgrades.